2006
DOI: 10.1152/ajpcell.00354.2005
|View full text |Cite
|
Sign up to set email alerts
|

CGRP inhibits osteoprotegerin production in human osteoblast-like cells via cAMP/PKA-dependent pathway

Abstract: The osteoprotegerin (OPG)/receptor activator of nuclear factor-κB ligand (RANKL)/receptor activator of nuclear factor-κB (RANK) system was evaluated as a potential target of CGRP anabolic activity on bone. Primary cultures of human osteoblast-like cells (hOB) express calcitonin receptor-like receptor (CLR) and receptor activity modifying protein 1, and, because CGRP stimulates cAMP (one of the modulators of OPG production in osteoblasts), it was investigated whether it affects OPG secretion and expression in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 53 publications
2
51
1
Order By: Relevance
“…BMP-2 promotes the proliferation of pre-osteoblast cells, induces the osteogenic or chondrogenic differentiation of mesenchymal cells [17,18] , and improves the osteogenic phenotype and capacity of stem cells through increased ALP activity and osteocalcin mRNA expression. Signal transduction studies have revealed that the Smad and P38MAPK pathways are immediately downstream of BMP receptors and that they play central roles in BMP signal transduction [4,[19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BMP-2 promotes the proliferation of pre-osteoblast cells, induces the osteogenic or chondrogenic differentiation of mesenchymal cells [17,18] , and improves the osteogenic phenotype and capacity of stem cells through increased ALP activity and osteocalcin mRNA expression. Signal transduction studies have revealed that the Smad and P38MAPK pathways are immediately downstream of BMP receptors and that they play central roles in BMP signal transduction [4,[19][20][21] .…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have demonstrated that CGRP stimulates osteoblast proliferation, differentiation and maturation in both osteoblast cell lines and bone marrow mesenchyme stromal cells. CGRP and its receptors have been identified in the [Ca 2+ ] i (intracellular Ca2 + ) [3] , cAMP (cyclic adenosine monophosphate) [4] , PKC (protein kinase C) [5] , MAPK (mitogen-activated protein kinase) [2,6] , and ERK (extracellular signal-regulated protein kinase) signal transduction pathways [7] .…”
Section: Introductionmentioning
confidence: 99%
“…CRE is essential for the response of the calcitonin/CGRP gene promoter 12), 13) . Villa et al reported that CGRP enhances PKA activity in human osteoblast-like cells and inhibits osteoprotegrin production through the CGRP receptor 28) . To examine whether CREB activation in cells cultured with CGRP mediates the CGRP receptor, Huh7 cells were precultured with the CGRP receptor antagonist CGRP .…”
Section: Discussionmentioning
confidence: 99%
“…Both calcitonin and CGRP have been shown to inhibit the maturation of osteoclasts induced by RANKL [77]. Nevertheless, CGRP can also inhibit the synthesis of osteoprotegerin by osteoblasts, suggesting a bimodal, autoregulatory, action [78]. This is echoed by the finding that CGRP (as well as substance P) can induce in vitro formation of the pro-inflammatory cytokines, IL-1, IL-6 and TNF-α, in human dental pulp cells [79].…”
Section: Distal Symmetrical Neuropathymentioning
confidence: 99%